Rachunkowość zarządcza a ryzyko działalności gospodarczej konglomeratu bankowo-ubezpieczeniowego : kontekst informacyjny - Duda, Ryszard (Management Accosting and Risk of the Business Activity of the Bank-Assurance Group : Information Context, 2007)
In this article the faults and advantages of the bank-assurance are presented. The rise of the magazine of knowledge of bank-assurance is discussed with the purpose of the implementation of the new insurance product for the market behind means of Internet. The expenses of management of the new insurance product on the market behind means of Internet marketing are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 95-111